Simulated near-field mapping of ripple pattern supported metal nanoparticles arrays for SERS optimization. (23rd October 2017) - Arya, Mahima; Bhatnagar, Mukul; Ranjan, Mukesh; Mukherjee, Subroto; Nath, Rabinder; Mitra, Anirban
Abstract: An analytical model has been developed using a modified Yamaguchi model along with the wavelength dependent plasmon line-width correction. The model has been used to calculate the near-field response of random nanoparticles on the plane surface, elongated and spherical silver nanoparticle arrays supported on ion beam produced ripple patterned templates. The calculated near-field mapping for elongated nanoparticles arrays on the ripple patterned surface shows maximum number of hot-spots with a higher near-field enhancement (NFE) as compared to the spherical nanoparticle arrays and randomly distributed nanoparticles on the plane surface. The results from the simulations show a similar trend for the NFE when compared to the far field reflection spectra. The nature of the wavelength dependent NFE is also found to be in agreement with the observed experimental results from surface enhanced Raman spectroscopy (SERS). The calculated and the measured optical response unambiguously reveal the importance of interparticle gap and ordering, where a high intensity Raman signal is obtained for ordered elongated nanoparticles arrays case as against non-ordered and the aligned configuration of spherical nanoparticles on the rippled surface.